2016
DOI: 10.1037/fam0000136
|View full text |Cite
|
Sign up to set email alerts
|

Parental emotional competence and parenting in low-income families with adolescents.

Abstract: Ample research has demonstrated that alexithymia, which is characterized by difficulty processing emotions, is associated with disruptions in parenting infants and toddlers. Individuals suffering from alexithymia have among other negative outcomes difficulty building and maintaining interpersonal relationships. Research on emotional expression and recognition has documented the importance of these competencies for the quality of the parent-child relationship and for skills critical for parents of adolescents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(77 reference statements)
1
2
0
1
Order By: Relevance
“…Research indicates that meta-emotion philosophy mediates the relationship between emotion coaching and children's social competence [48] and that better parent emotion coaching skills are associated with higher child emotional competencies [49]. This corroborates findings from research on parent modeling and socialization, which has linked parental alexithymia to child outcomes such as lack of emotional and social competence [48][49][50]. Thus, the current study proposes a pathway (Fig.…”
Section: Intergenerational Transmission Of Alexithymia (Fig 1 Path A)supporting
confidence: 85%
“…Research indicates that meta-emotion philosophy mediates the relationship between emotion coaching and children's social competence [48] and that better parent emotion coaching skills are associated with higher child emotional competencies [49]. This corroborates findings from research on parent modeling and socialization, which has linked parental alexithymia to child outcomes such as lack of emotional and social competence [48][49][50]. Thus, the current study proposes a pathway (Fig.…”
Section: Intergenerational Transmission Of Alexithymia (Fig 1 Path A)supporting
confidence: 85%
“…Some recent work in this area (e.g., Borre & Kliewer, 2014) showed that parents’ exposure to violence and their overall stress levels affect their mental health, which in turn affects parenting. Further, parents’ emotional competence is prospectively associated with parental monitoring and perceived parental acceptance among low-income, urban adolescents (Kliewer et al, 2016). Additional research may wish to include all components of parental monitoring (e.g., parental control and parental knowledge) to examine how all of these monitoring constructs work together to affect adolescent externalizing behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of this hypothesis, literature suggests the existence of a potential intergenerational transmission of the difficulty in emotional regulation from parents to their children ( Lumley et al, 1996 ; Fukunishi and Paris, 2001 ; Guttman and Laporte, 2002 ; Kliewer et al, 2016 ). Nevertheless alexithymia along with parental bonding have been usually studied only at the individual level both in the general population and in psychiatric patients, including recently adolescents too.…”
Section: Introductionmentioning
confidence: 99%